P3-S1.13 Establishment of a protocol for the detection of Chlamydia trachomatis in semen specimens using the cobas® 4800 CT/NG test. (10th July 2011) - de Barbeyrac, B; Mehats, V; Papaxanthos, A; Bébéar, C
Abstract : Background: In addition to common urogenital samples, semen specimens are used to detect Chlamydia trachomatis (CT). In France, testing of semen specimens is mandatory by law in context of donors and in vitro fertilisation. However, semen specimens are known to show significant inhibition in PCR assays. Analysis of cycles of threshold (ct) values can be used to determine inhibition and limits of detection of assays. Objective: To establish a suitable protocol for the highly sensitive detection of CT in semen specimens using the fully automated cobas 4800® CT test. Materials and Methods: We evaluated inhibition rates and limits of detection (LOD) for different semen sample volumes by ct value analysis in the cobas® 4800 CT test. Semen samples were obtained from 100 patients visiting the reproduction biology department of the Bordeaux University hospital. Between 5 and 67 replicates of semen ranging from 1 to 50 μl were each added to 4.5 ml of cobas® PCR media and run in the cobas® 4800 CT test. The inhibition rate was compared to the inhibition rate obtained in 323 urogenital swabs and 278 urines using the ct values of the internal control (IC). Thereafter, semen volumes that showed the lowest inhibition rates were selected to determine the LOD, by comparing mean ct values for the target in the cobas® 4800 CT test using semen specimens spiked with different concentrations of CT. Results: Mean IC ct values in semen volumes ranging from 1 to 40 μl did not differ from those obtained in urogenital swabs and urines, whereas semen volumes of 50 μl resulted in a marked increase in IC ct values indicating inhibition. Therefore, semen volumes of 25, 40, and 50 μl diluted in 4.5 ml of cobas® PCR media were tested to determine the LOD. Mean ct values generated by the target CT are shown in Abstract P3-S1.13 table 1 . Ct values were similar in samples of 25 μl semen and controls, but were higher or even negative in 40 and 50 μl semen volumes indicating that a semen volume of 25 μl showed the lowest LOD (10–5) combined with a low inhibition rate. Conclusion: Semen specimens can be tested in the cobas® 4800 CT test applying our easy to perform, highly sensitive, and low inhibition protocol.